Global Wild Poliovirus and cVDPV drop during COVID Pandemic. Why and How? - Kazi, Zaubina; Pethani, Asma; Saleem, Ali Faisal (Infectious Diseases Journal of Pakistan, 2022)
Wild Poliovirus (PV) is now limited to only two endemic countries (Pakistan and Afghanistan). Concerns related to polio outbreaks during COVID times are vanishing as the cases (wild PV and circulating Vaccine-derived PV) have reduced remarkably. This seems like a program success. Meanwhile, there are concerns if this drop is not accurate. We hypothesize that this observed decrease is actual and not a result of worsening PV surveillance. We propose a few theories: 1) Programmatic success leading to exhaustion of susceptible population, 2) Decrease in social contacts due to COVID leading to a reduction in opportunities to transmit for both WPV and cVDPV, 3) In endemics, “Receptor Competition” between PV2 and WPV1 leading to initial predominance of PV2 infections (through either VDPV2 transmission or use of tOPV), which reduced WPV1 ability to infect, and lastly 4.) a Sub-clinical infection in wPV1 reservoirs leading to natural immunity to high-moderate risk individual.